La cultura tributaria y su incidencia en la recaudación de impuestos municipales del gobierno autónomo descentralizado del cantón Latacunga. - Maigua Tiglla, Julio Francisco (2019)
The main objective of this research was to analyze the impact of tributary culture on the collection of municipal taxes of the Decentralized Autonomous Government of the canton Latacunga, through a specific study containing conclusions and recommendations. The research has a quantitative design; this allows us to collect Information to test the hypothesis between two variables; besides, the modality is field and documentary. The sample was selected through the statistical formula for finite populations, resulting in 383 contributors. The Information collected in the fieldwork through questionnaire research tool, as well as interview with an official of the municipal GAD of Latacunga with specific questions to know its opinion on tributaries culture and the collection of municipal taxes, the research is complemented by an analysis of the collection of property tax in the years 2017 and 2018. In the interview with the judge of coercive, said that the municipality of the city of Latacunga is planning strategies to train taxpayers through radio programs, notifications, and agreements with higher education institutions, all to strengthen the tributaries culture in the city, in order to improve the collection of municipal taxes. On the other hand, in the survey applied to taxpayers, the in-depth knowledge in tax matters could be noted. One percentage of 64.2% of respondents said, "The lack of information on the part of the municipality." Also, a percentage of 63.7% cancels their municipal taxes on time due to economic situation or lack of time. The main result of the property tax analysis shows that in 2017 there was an overdue portfolio of $575,664.07, while in 2018 it was $643,430.83 in both cases representing 21% in relation to securities issued for property tax, finally with the statistical test Chi-squared it was possible to show that the tributaries culture influences the collection of municipal taxes.